Penghapusan Pidana Penjara dengan Minimum Khusus untuk Independensi Hakim dan Mengurangi Overcrowded di Lembaga Pemasyarakatan - sultan rambe (Jurnal Hukum Lex Generalis, 2026)
Minimum sentences are regulated under Law No. 1 of 2023 on the Indonesian Criminal Code. This provision reflects a retributive paradigm that may hinder the development of a criminal justice system oriented toward restorative justice. This study aims to analyze the current relevance of minimum sentences. It employs a normative juridical method using statutory, case and comparative approaches. The findings indicate that minimum sentences limit judicial independence in delivering proportionate decisions and contribute to prison overcrowding, highlighting the need to eliminating minimum sentences.